Multi-parent QTL mapping reveals stable QTL conferring resistance to Gibberella ear rot in maize - Galiano Carneiro, Ana L. (2020)
Maize production is on risk by Gibberella ear rot (GER) caused by Fusarium graminearum. This is one of the most important ear rot diseases in temperate zones as it leads to yield losses and production of harmful mycotoxins. We investigated, for the first time, the potential use of Brazilian tropical maize to increase resistance levels to GER in temperate European flint germplasm by analyzing six interconnected biparental populations. We assessed GER symptoms in Brazil and in Europe in up to six environments (= location × year combinations) during the growing seasons of 2018 and 2019. We conducted multi-parent QTL and biparental QTL mapping, and identified four QTLs with additive gene action, each explaining 5.4 to 21.8% of the total genotypic variance for GER resistance. Among them, QTL q1 was stable across test environments, populations, and between inbred lines and testcrosses. The accuracies of genomic prediction ranged from 0.50 to 0.59 depending on the resistance donor and prediction model. Jointly, our study reveals the potential use of Brazilian resistance sources to increase GER resistance levels by genomics-assisted breeding.